Contribution of Skill and Knowledge of Return Migrant Workers in Economic Productive Sectors - Yakha, Kamal Kumar (Economic Review of Nepal, 2021)
This study focuses on contribution of skill and knowledge of return migrant workers in economic productive sectors. It examined of acquired learn skills and knowledge are transferred by migrant workers from origin and the destination country. In the study areas, the purposive sampling method was used. However, census method, was used only the purpose of selecting are identifying household survey in the study area. It includes those migrants who have migrated to foreign employment at least stay 6 months for work for the last 5 years. However, from the total selected households were taken total 275 of the migrant respondents. Primary and secondary data were used in this study. In this study, both descriptive and analytical analysis approach were used. Similarly, qualitative information and quantitative data were used for this study purpose. Pilot survey was also conducted for purpose of selection of household. The study indicated that the majority of respondents were concluded to establish in agriculture / livestock. Similarly, higher volumes of migrant workers found in less than 2 lakha investment of remittances to established in enterprise. In large number of respondents haired two and three or more workers only part time work purpose. However, most of enterprises involved one worker regularly. In large numbers of respondents earn income higher less than twenty thousand per month in enterprise business. Majority of migrants purchased their earning income money on basic needs and to pay loans. Furthermore, most of respondents changed to improve in livelihood for basic needs of household family/ community. So, the research can be conducted skills and knowledge transformation on productive works for economic contribution purpose.